Konsep Maisir dalam Pandangan Fukaha dan Relevansinya pada Asuransi Konvensional: The Concept of Maisir in the View of Fuqaha and Its Relevance to Conventional Insurance - Gozaly, Ahmad Yusdi; Dheddy Abdi Tamba; Nurrohman Syarif (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This study aims to analyze the concept of maisir in Islam according to the views of the fuqaha and then relate it to conventional insurance and sharia insurance and the relevance of the concept of maisir in the context of conventional insurance in Indonesia, which is increasingly developing along with the needs of financial protection for the community. This research uses an analytical descriptive method which aims to analyze certain objects, conditions, or phenomena in natural or real conditions (without experiments) to compile a systematic overview and provide detailed, factual, and accurate descriptions. This type of research is a type of library research by reviewing the opinions of Ulama on the concept of maisir according to Fuqaha in the Fiqh literature and then reviewing its relevance to conventional insurance practices. The results of the study indicate that conventional insurance contains elements of maisir, because in practice there are aspects of speculation of chance so that it is possible for the perpetrators to be in two unclear states between profit or loss. This is because conventional insurance uses a tijari contract instead of a tabarru' contract. Therefore, this study recommends the development of a sharia-based insurance model based on the principle of ta'awun (mutual assistance) and fair risk sharing in order to provide an alternative that is in accordance with Islamic law.